Self-perception evolution among university student TikTok users: evidence from China - Zhu, Jinsheng (Jason); Ma, Yan; Xia, Guoen; Salle, Sabariah Mohamed; Huang, Hongye; Sannusi, Shahrul Nazmi (Frontiers in Psychology, 2024)
The effects of short movies on social media platforms are gaining worldwide popularity and are now attracting global academic attention. Employing self-perception theory and qualitative research methodology, the study examines the influence of short video applications (TikTok) on app-user engagement and evaluates the self-perceived cognitive psychological understanding of Chinese university students. The findings show that identity, attitude change, emotional perception, and civic engagement are the most influential aspects of Chinese youths’ self-perceptions. Furthermore, the positive and negative correlated components influence the distribution of short video values. Such tactical use of personality construction contributes to the present psychological research of Chinese university students.